Bacteria from Salt Pans: A Potential Resource of Antibacterial Metabolites - Savita Kerkar*, Tonima Kamat and (Recent Research in Science and Technology, 2011)
Marine salt pans are important ecological niches which inhabit halobacteria. These bacteria tolerate and thrive in salt concentrations ranging from 0.5 to more than 5 M in which only very few other organisms are able to survive. Bacteria from marine salt pans of varying salinities of 220 to 395 psu were isolated during the peak salt harvesting season and screened to evaluate their antibiotic producing potential. In this report, a total of 119 bacteria were screened on 12 different solid media supplemented with either natural salt or sea water or distilled water to check their substrate utilization and salinity requirement. Based on their morphological variations, 94 isolates were further screened for their antagonistic properties, against 20 different clinical pathogens. Thirty one isolates were found to produce antibacterial compounds of which, 21 showed bactericidal action and one was bacteriostatic while 9 isolates exhibited both bacteriostatic and bactericidal activity. Eleven isolates were broad spectrum antibiotic producers. This study provides information regarding the applied value of potential halotolerant and halophilic isolates as pharmaceutically important microorganisms.